Characterisation of asymptomatic patients and efficacy of preventive measures for SARS-CoV-2 infection in a large population of Southern Italy: a cohort study. Issue 5 (10th May 2021) - Masarone, Mario; Vaccaro, Emilia; Sciorio, Roberta; Torre, Pietro; Della Vecchia, Antonio; Aglitti, Andrea; Caliulo, Rita; Borrelli, Anna; Persico, Marcello
Abstract : Background: The SARS-CoV-2 pandemic has infected millions of people and has caused more than 2.30 million deaths worldwide to date. Several doubts arise about the role of asymptomatic carriers in virus transmission. During the first epidemic outbreak in Italy a large screening with nasopharyngeal swab (NS) was performed in those who were considered 'suspect' for infection. Aims: To report the results of the SARS-CoV-2 screening in a province in Southern Italy and to provide data on the COVID-19 epidemic and the burden of asymptomatic subjects. Patients and methods: A retrospective cohort study was set up in all healthcare facilities of the province (12 hospitals and 13 sanitary districts: primary, secondary and tertiary centres) with the aim to analyse the results of NS performed on all subjects suspected to be infected with SARS-CoV-2, either because they presented symptoms suggestive of SARS-CoV-2 infection, they were 'contacts' of positive subjects, they came from areas with high prevalence or they were healthcare workers. NS were performed and managed as indicated by international guidelines. The specimens were processed for SARS-CoV-2 detection by real-time PCR. Results: A total of 20 325 NS were performed from 13 March to 9 May 2020. Of these, 638 (3.14%) were positive. 470 were asymptomatic, or 75.3% of persons who were positive. They were mostly among 'contacts' of symptomatic cases (428 of 470, 91%) and were in domiciliary isolation. Expression of three SARS-CoV-2 genes did not differ between asymptomatic and symptomatic subjects. The strict measures with regard to social distancing led to a continuous decrease in cases during phase 1. Conclusions: In a large area in Southern Italy, 3.14% (638 of 20 325) of the total subjects tested were positive for SARS-CoV-2. Most of them were asymptomatic (470 of 624, 75.3%), and of these 91% (428 of 470) were 'close contacts' of symptomatic subjects. The combination of social distancing together with the systematic screening of close contacts of COVID-19-positive symptomatic subjects seems to be an efficacious approach to limit the spread of the epidemic.